Monitoring Radiofrequency Ablation Using Ultrasound Envelope Statistics and Shear Wave Elastography in the Periablation Period: An In Vitro Feasibility Study - Tsui, Po-Hsiang (PLoS One, 2016)
Radiofrequency ablation (RFA) is a minimally invasive method for treating tumors. Shear wave elastography (SWE) has been widely applied in evaluating tissue stiffness and final ablation size after RFA. However, the usefulness of periablation SWE imaging in assessing RFA remains unclear. Therefore, this study investigated the correlation between periablation SWE imaging and final ablation size. An in vitro porcine liver model was used for experimental validation (n = 36). During RFA with a power of 50 W, SWE images were collected using a clinical ultrasound system. To evaluate the effects of tissue temperature and gas bubbles during RFA, changes in the ablation temperature were recorded, and image echo patterns were measured using B-mode and ultrasound statistical parametric images. After RFA, the gross pathology of each tissue sample was compared with the region of change in the corresponding periablation SWE image. The experimental results showed that the tissue temperature at the ablation site varied between 70°C and 100°C. Hyperechoic regions and changes were observed in the echo amplitude distribution induced by gas bubbles. Under this condition, the confounding effects (including the temperature increase, tissue stiffness increase, and presence of gas bubbles) resulted in artifacts in the periablation SWE images, and the corresponding region correlated with the estimated final ablation size obtained from the gross pathology (r = 0.8). The findings confirm the feasibility of using periablation SWE imaging in assessing RFA.